2003
DOI: 10.17221/3482-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of wheat and flour Zeleny sedimentation value using NIR technique.

Abstract: Wheat and flour quality is expressed by a variety of chemical and physical properties of dough, none of which serves as adequate by itself or is independent of others variables (P���� 1988). According to F����� (1978) "a flour of good quality for breadmaking should have high water absorption, a medium to medium -long mixing requirement, satisfactory mixing tolerance, and bread volume potential (considering protein content), and should yield a loaf with good internal grain and colour". T������ et al. (1982) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 4 publications
4
42
0
Order By: Relevance
“…Similar relationships have been reported by Martin et al (2001), Hruškova and Famĕra (2003), and Jirsa et al (2008). In present study, a negative correlation was found between grain yield and quality characteristics; this confirms the association between those traits (see, e.g., Kleijer et al 2007, Oury and Godin 2007, Bordes et al 2008.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar relationships have been reported by Martin et al (2001), Hruškova and Famĕra (2003), and Jirsa et al (2008). In present study, a negative correlation was found between grain yield and quality characteristics; this confirms the association between those traits (see, e.g., Kleijer et al 2007, Oury and Godin 2007, Bordes et al 2008.…”
Section: Discussionsupporting
confidence: 91%
“…Grain hardness (GH), hectoliter weight (HW) and some parameters related to bread-making quality: protein (PC), starch (SC) and wet gluten (WG) content, Zeleny sedimentation value (ZS) and alveograph W parameter (AWP) were analyzed using a NIRSystems Infratec 1241 Grain Analyzer (Foss, Hillerod, Denmark) (Hruškova and Famĕra, 2003;Osborne, 2006;Silva et al, 2008). (The Obuchowski et al (2010): H−hard, S−soft, M−"medium".…”
Section: Grain Quality Analysismentioning
confidence: 99%
“…The Zeleny sedimentation test can give valuable information about the baking quality of wheat too. Higher gluten content and a better gluten quality give rise to slower sedimentation and higher Zeleny test values 21…”
Section: Resultsmentioning
confidence: 99%
“…Hruskova and Famera (2003) evaluated 318 wheat samples for Zeleny sedimentation value through an NIR technique and found they ranged from 17 to 66 mL. The SDS-sed test is an estimate of the strength of the wheat (gluten quality) and it depends upon the degree of hydration of the proteins in the wheat and on their degree of oxidation.…”
Section: Chemical Characteristicsmentioning
confidence: 99%